(untitled) (The International Journal for Scientific Research, 2024)
This paper studies the hyponormality of Toeplitz Operators with Trigonometric Polynomial Symbols to find conditions on the coefficients that are necessary and sufficient for Toeplitz Operators to be hyponormal.